Sense of coherence as a protective factor in chronic urticaria - Ograczyk, Alicja; Miniszewska, Joanna; Pietrzak, Anna; Zalewska-Janowska, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction: Chronic urticaria (CU) seems to be perceived as a psychodermatological disorder. Different psychological factors play an important role in CU triggering and course. One of them is a sense of coherence (SOC), which is believed to be a protective factor against anxiety and depression. Aim : To investigate quality of life (QoL) in CU patients and to compare selected psychological parameters (anxiety, depression and sense of coherence) between CU individuals and the control group. Material and methods : The study comprised 46 female patients with chronic urticaria and 33 healthy females as a control group. The following methods were employed: Urticaria Activity Score (UAS), Hospital Anxiety and Depression Scale (HADS), Sense of Coherence Questionnaire (SOC-29) and Dermatology Life Quality Index (DLQI). Results : The CU patients presented a significantly higher anxiety level in comparison to the control group (z = 4.488; p < 0.001). There were no statistically significant differences regarding depression intensity and SOC. In both groups anxiety and depression negatively correlated with global SOC and all its components. Disease severity positively correlated with QoL ( = 0.46, p < 0.01) and negatively with global SOC ( = –0.33, p < 0.05). Conclusions : Bearing in mind higher prevalence of anxiety and depressive symptoms in our CU group, it would be useful to perform screening of these aspects in all CU patients and subsequently develop respective psychological interventions, based on enhancement of personal resources.